The Use of Three Species of Lactic Acid Bacteria in the Mocaf (Modified Cassava Flour) Production - Seveline, Seveline; Heldyana, Riskya; Kurniawati, Siti (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractThe use of cassava as foodstuffs has been widely developed. Modifying it into a mocaf (modified cassava flour) is one of the cassava utilization. This research aimed to process cassavas into mocaf utilizing lactic acid bacteria and to obtain a better mocaf in terms of its physicochemical parameters. Bacteria used were L. plantarum, L. fermentum, and L. paracasei, which can ferment cassava to mocaf. The fermentation process was carried out by two fermentation duration of 48 hours and 72 hours, followed by draining and drying using the oven at 50 °C for 6 hours. This research analyzed mocaf's physicochemical properties such as water content, fat content, protein content, ash content, carbohydrate content, whiteness, and acidity. A Factorial Randomized Block Design with two replications was applied as the research design. If the test result showed that the tested sample has a significant difference at the level of significance of 0.05, it then subjects to the further Duncan test, using SPSS. The result showed that the use of L. paracasei produced best characteristics mocaf with a high protein content of 1.44%, an ash content of 0.31%, a white degree of 102.20, and a low degree of acid of 3.66.Keywords: cassava, fermentation duration, L.fermentum, L.paracasei, L.plantarum AbstrakPenggunaan ubi kayu sebagai bahan pangan telah banyak dikembangkan. Salah satu cara dalam pemanfaatan ubi kayu adalah dengan mengolah menjadi produk berupa mocaf (modified cassava flour). Penelitian ini bertujuan untuk mengolah ubi kayu menjadi mocaf dengan bantuan bakteri asam laktat dan mendapatkan hasil tepung mocaf yang lebih baik dari segi fisikokimianya. Bakteri asam laktat yang digunakan adalah L. plantarum, L. fermentum dan L. paracasei yang ternyata memiliki kemampuan dalam memfermentasi ubi kayu menjadi mocaf. Proses fermentasi ubi kayu dilakukan selama dua waktu fermentasi, yaitu 48 jam dan 72 jam yang kemudian dilanjutkan dengan penirisan dan pengeringan dengan oven pada suhu 50 °C selama 6 jam. Analisis dilakukan pada beberapa sifat fisikokimia dari tepung mocaf berupa kadar air, kadar lemak, kadar protein, kadar abu, kadar kabohidrat, derajat putih dan derajat asam. Rancangan penelitian yang digunakan adalah Rancangan Acak Kelompok Faktorial dengan dua kali ulangan. Jika hasil uji menyatakan bahwa sampel yang diujikan berbeda nyata pada taraf kepercayaan 0,05, maka akan dilakukan uji lanjut Duncan dengan menggunakan SPSS. Hasil yang didapat pada penggunaan L. paracasei menghasilkan tepung mocaf dengan karakteristik terbaik, kadar protein yang tinggi sebesar 1,44%, kadar abu 0,31%, derajat putih 102,20 dan derajat asam yang rendah sebesar 3,66.Kata kunci: L. fermentum, L. paracasei, L. plantarum, lama fermentasi, ubi kayu